Effect of Binary Solvent Mixtures on Ion-Pair Formation and Solvation Dynamics - Dr. Rakesh Ranjan Raj (International Journal of Scientific Research in Science and Technology, 2024)
This study determines the impact of binary solvent mixtures, particularly water and Dimethylformamide (DMF), on the formation of the ion-pair and dynamic solvation. The ion interaction dynamics of halides and nitrates with M²⁺ and M³⁺ have been assessed through conductivity studies and also ion-pair stability in addition to assessing solvation thermodynamics by varying the temperature. Experiments along with theoretical understanding lead the paper to highlight the critical modulatory effect of solvent polarity, hydrogen bonding, and viscosity of the medium affecting ion-ion interactions and finally, structures of solvation.
Keywords: Raman Spectroscopy; Dimethylformamide (DMF); Correlation of Dielectric and Hydrogen Bonding; Solvation Dynamics; Binary Solvent Mixtures; Ion-Pair Formation